Modeling Fertilizer Demand in Cotton-Producing Villages of Benin: Does Price Matter in a Centralized Distribution System? - Honfoga, Barthelemy G. (European Scientific Journal, ESJ, 2016)
Cotton is a strategic crop in Benin's economy and fertilizer is a crucial necessity for its development. Fertilizer supply is awkwardly cotton-oriented and depends totally on imports. Spurious liberalization, characterized by partial state withdrawal combined with a rigid distribution agreement between the state, fertilizer traders and farmers’ cooperatives, led to a drastic decline in fertilizer use and cotton production. Although fertilizer consumption resumed timidly with reforms, the supply system remained centralized (importers’ licensing, distribution quotas, price administration). This study inquired whether price is relevant in fertilizer demand in such a business environment. Randomly-selected 577 cotton farmers from purposively-chosen 191 cotton-producing villages, were interviewed about fertilizer use and distribution using structured questionnaires. Determinants of average villagelevel fertilizer demand, elicited using a multiple regression model with a joint agronomic and marketing perspective, included at 5% or 1% significance level: the region’s dummy, share of cotton in cultivated area, rural roads’ density, distance ‘village store - farmer’s fields, and off-farm income. Other non-negligible factors included: estimated cost price, soil degradation rate, diffusion rate of water and soil conservation techniques, proportion of leased land area and distance ‘farmer’s house - local agricultural market’. Despite an administered pan-territorial district-level price, fertilizer demand was still sensitive to the actual farm-gate prices. However, the business environment had a stronger influence. The policy levers to increase fertilizer use intensity include the development of road and market infrastructures, promotion of market orientation of farming and off-farm activities, wise liberalization of fertilizer retail market, and reform of the licensing system.